Effectiveness of long-acting risperidone in a patient with comorbid intellectual disability, catatonic schizophrenia, and oneiroid syndrome. (October 2015) - Serata, Daniele; Rapinesi, Chiara; Demetrios Kotzalidis, Georgios; Chiara Alessi, Maria; Janiri, Delfina; Claudia Massolo, Anna; Rachele Ferri, Vittoria; Criscuolo, Silvia; Callovini, Gemma; Angeletti, Gloria; Girardi, Paolo; Del Casale, Antonio
A patient with comorbid intellectual disability, catatonic schizophrenia, and recurrent oneiroid state of consciousness improved on long-acting risperidone and remains well at the three-year follow-up. We report a case treated with 50 mg long-acting risperidone administered every 14 days, who has been followed-up for three years. We studied his regional cerebral blood flow through technetium-99 m hexamethylpropyleneamine oxime single-photon emission computed tomography after two years of treatment. Symptoms of catatonic schizophrenia improved after two months of treatment, followed suit by oneiroid syndrome remission. Two years later, his brain perfusion was normal. No side effect has occurred since the patient was started on long-acting risperidone. Long-acting risperidone proved to be safe and effective in treating symptoms of catatonia and oneiroid syndrome.